Does triclosan adsorption on polystyrene nanoplastics modify the toxicity of single contaminants?. Issue 1 (23rd December 2020) - Parenti, C. C.; Magni, S.; Ghilardi, A.; Caorsi, G.; Della Torre, C.; Del Giacco, L.; Binelli, A.
Abstract : The risk associated to the action of nanoplastics as carriers of environmental pollutants was investigated by a multi-tiered approach. Abstract : The physical and chemical properties of nanoplastics make them potential carriers for some environmental contaminants, modifying their biological effects. Nevertheless, the change in toxicity caused by pollutant adsorption on nanoplastics is still controversial, depending on the interactions between chemical and physical pollutants, the consequent change in bioavailability, the modification of intake, transport and accumulation in the organisms and also on the characteristics of contaminants. In this context, the aim of the present study was the evaluation of combined effects made by 0.5 μm nanobeads of polystyrene and triclosan adsorbed on their surface in comparison with those caused by single contaminants. The systemic effects of 7 day exposure to nanoplastics, triclosan alone and to the nanoplastic–triclosan complex have been analyzed by employing zebrafish larvae and using a multi-tier approach from the evaluation of cellular and molecular effects to the impact at organism level. Results highlighted by confocal microscopy evidenced nanobead ingestion and translocation in several tissues and organs to guarantee the goodness of the exposure results. Behavioral assays were then conducted to highlight larval swimming defects as a 'real-time' readout of the potential effects on the whole organism, while a suite of several biomarkers and functional proteomics was applied to investigate the effects at both cellular and molecular levels. The whole data set pointed out a clear modification in the toxicological effects of the nanoplastic–triclosan complex in comparison with single contaminants, proved by opposite behaviours in the larval swimming activity and modulation of diverse protein classes as well as by different effects on several biochemical endpoints. This means that the interaction between chemical and physical pollutants leads to more complicated responses than additive, synergistic or antagonist models, resulting in a modification of toxicity instead of its increase or decrease.